Social Seed Networks for Climate Change Adaptation in Uganda: Strategies to Improve Access to Genetic Diversity and Information. Results from a study to better understand farmers’ primary sources of seed and information in the Hoima Climate-Smart Villages - Otieno, Gloria Atieno; Lacasse, Hannah; Adokorach, Joyce; Mulumba, John W.; Recha, John W.M.; Reynolds, Travis W.; Fadda, Carlo (2018)
Climate change poses serious threats to smallholder farmers in Uganda. For instance, rains often start late in the season and end early, reducing the growing season. Increasing and maintaining genetic diversity is one way of combatting these climatic change-related threats (IPCC, 2014). Farmers often manage, select, and conserve genetic diversity according to their needs, but climate change is quickly eroding this genetic diversity. Accessing genetic resources and related information is therefore paramount to farmers’ ability to cope with the effects of climate change. Farmers’ seed networks are a crucial element of access to seed because they are resilient and help to maintain and conserve crop genetic diversity (Pautasso et al. 2013). In Uganda, 85% of the seed is from ‘informal’ sources consisting of seed saved from own farm as well as seed obtained from neighbours and other local sources. Research in East Africa has suggested that community-generated information sharing might support more effective farmer response to the changing seasonal and weather patterns associated with climate change (Adhikari et al. 2015). However, the influence of Ugandan farmers’ social networks in supporting adaptation to climate change is not well known.